اسلام اور پیغمبر اسلام : غیر مسلم مطالعہ کے مناہج و اسالیب اور اثرات کاتجزیاتی مطالعہ: Islam and the Prophet Muhammad: A Study of Non-Muslim Approaches, Methods, Effects - An Analytical Study - Areeba Farooq; Aneeqa Waheed; Umer Yousaf (International Research Journal of Arabic and Islamic Studies, 2024)
This analytical study delves into the approaches, methodologies, and impacts of non-Muslim inquiry into Islam and the Prophet Muhammad. It explores how non-Muslim scholars have engaged with Islamic topics, examining the methods they employ and the effects these inquiries have had. By scrutinizing these aspects, the study aims to provide insights into the dynamics of cross-cultural engagement with Islam and its central figure, the Prophet Muhammad. This examination not only highlights the academic rigor and perspectives brought by non-Muslim scholars but also considers the broader cultural and social implications of their work. Through this comprehensive analysis, the study seeks to contribute to a deeper understanding of interfaith scholarship and its role in shaping contemporary discourse on Islam.